COVID-19 update: The race to therapeutic development (2020)
The COVID-19 pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARSCoV-2), represents an unprecedented challenge to global public health. At the time of this review, COVID-19 has been diagnosed in over 40 million cases and associated with 1.1 million deaths worldwide. Current management strategies for COVID-19 are largely supportive, and while there are more than 2,000 interventional clinical trials registered with the U.S. National Library of Medicine (clinicaltrials.gov), results that can clarify benefits and risks of candidate therapies are only gradually becoming available. We herein describe recent advances in understanding SARSCoV-2 pathobiology and potential therapeutic targets that are involved in viral entry into host cells, viral spread in the body, and the subsequent COVID-19 progression. We highlight two major lines of therapeutic strategies for COVID-19 treatment: 1) repurposing the existing drugs for use in COVID-19 patients, such as antiviral medications (e.g., remdesivir) and immunomodulators (e.g., dexamethasone) which were previously approved for other disease conditions, and 2) novel biological products that are designed to target specific molecules that are involved in SARS-CoV2 viral entry, including neutralizing antibodies against the spike protein of SARS-CoV-2, such as REGN-COV2 (an antibody cocktail) and LY-CoV555, as well as recombinant human soluble ACE2 protein to counteract SARS-CoV-2 binding to the transmembrane ACE2 receptor in target cells. Finally, we discuss potential drug resistance mechanisms and provide thoughts regarding linical trial design to address the diversity in COVID-19 clinical manifestation. Of note, preventive vaccines, cell and gene therapies are not within the scope of the current review.